Դիվանագիտական լեզվի առանձնահատկություններն իսպաներենում - Աննա Հակոբյան (ՀՀ ԳԱԱ հրատ.)
The goal of this article is to present the main peculiarities of diplomatic language in Spanish. The present study analyzes the morfological and syntactical peculiarities of Spanish language in diplomacy, as well as the use of diplomatic terminology, abbreviations and cliches. The present paper deals with stylistic analysis of diplomatic language and reveals the stylistic features of diplomatic language in Spanish.
Keywords: Language and Literature